Contemporary German fiction : writing in the Berlin republic - Taberner, Stuart (Cambridge studies in German., 2007)
The profound political and social changes Germany has undergone since 1989 have been reflected in an extraordinarily rich range of contemporary writing. Contemporary German Fiction focuses on the debates that have shaped the politics and culture of the new Germany that has emerged from the second half of the 1990s onwards and offers the first comprehensive account of key developments in German literary fiction within their social and historical context. Each chapter begins with an overview of a central theme, such as East German writing, West German writing, writing on the Nazi past, writing by women and writing by ethnic minorities. The authors discussed include Günter Grass, Ingo Schulze, Judith Hermann, Christa Wolf, Christian Kracht and Zafer Senocak. These informative and accessible readings build up a clear picture of the central themes and stylistic concerns of the best writers working in Germany today.